Fully parallel algorithm for simulating dispersion-managed wavelength-division-multiplexed optical fiber systems - Lushnikov, P M (Optics letters, 2002)
An efficient numerical algorithm is presented for massively parallel simulations of dispersion-managed wavelength-division-multiplexed optical fiber systems. The algorithm is based on a weak nonlinearity approximation and independent parallel calculations of fast Fourier transforms on multiple central processor units (CPUs). The algorithm allows one to implement numerical simulations M/2 times faster than a direct numerical simulation by a split-step method, where M is a number of CPUs in a parallel network.